THE INDONESIAN DISABILITY NATIONAL COMMISSION AS A STRATEGIC POLICY IN FULFILLING THE RIGHTS OF PEOPLE WITH DISABILITY - Galuh Wahyu Kumalasari (Fakultas Hukum, Universitas Diponegoro, 2017)
The disability or different ability is every people who had physical limitation, intellectual, mental, and/or sensory for a long time in interacting with their environment, could run into obstacles and difficulties to participate in full and effective with other citizens by equality rights. The law 8/2016 about people with disability is being law enforcement to fulfill the rights for the people with disability. Social Affairs Ministry through the Social Directorate of Disability Rehabilitation is the instrument of the state to implement the fulfillment of the rights. This writing is used normative juridical method to dig the formation policy of the National Commission with Disability to guarantee the disability rights. This study found that function given to social affairs ministry actually flawed, considering rights of people with disabilities is not simply about economic needs, but also the right to life, health, education, accessibility, political, and others. There are so many disabilities in various areas experienced discrimination and treated very inhuman, not only related accessibility but also about neglect practices and put the people with disabilities in a stocks. The formation of a national commission with disability as instructed in article 131-134 Act 8/2016 is very urgent to crystallize, so the implementation of the disability rights can be optimized. The formation of the national commission with disability will give certainty of a special institution that focus to handle and ensure the fulfillment rights of people with disabilities as citizens.